Outage Analysis in SWIPT-Based Decode-and-Forward Relay Networks with Partial Relay Selection. (28th June 2021) - Tin, Phu Tran; Phan, Van-Duc; Nguyen, Phu X.; Nguyen, Thanh-Long; Chau, Dong-Si Thien; Nguyen, Tan N.
Abstract : This work studies the SWIPT-based half-duplex (HD) decode-and-forward (DF) relay network, wherein the relay user can scavenge power from the source's radio-frequency (RF) signals and then utilize it to convey the information to the destination. Specifically, two SWIPT-based relaying schemes, termed static power splitting- (SPS-) based relaying (SPSR) and optimal dynamic power splitting- (DPS-) based relaying (ODPSR), are proposed to investigate the benefits of each one fully. Based on the above discussions, the relaying system's performance for outage probability (OP) is studied. Concretely, we derive the analytical expressions for both SPSR and DPSR methods. Finally, the numerical simulations are executed to corroborate the analysis and simulation results.